Students’ Perceptions Toward English Teacher’s Teaching Strategies, Personal Competence, And School Facilities - Humairatul Hasanah; Nuri Hermawan (La Ogi : English Language Journal, 2022)
This study aims to investigate students' perceptions toward English teacher teaching strategies, personal competence, and school facilities at Mts Nurur Rahmah Pamekasan. This study use qualitative research. The sample of this study involved 25 students in class 7-9 junior high school at Mts Nurur Rahmah Pamekasan. In this study, the writer use some kinds of instruments; the researcher, observation and interview, note-taking, video camera, and document. The data would be taken from the observation. In addition, the writer also used online questionnaire (close-ended and open-ended question) to gain information about students’ perceptions on the teacher’s teaching strategies. The result shows that the teaching strategies are suggested to be used by teachers in their teaching process to attract students' interest in learning the target language and to achieve curriculum goal has not been fully implemented. The teacher did not apply the required strategies in English language teaching and did not have a set of complete personality. In addition, regarding school facilities, the schools do not have adequate facilities.